Penerapan Solar Cell (Pembangkit Listrik Tenaga Surya) Untuk Pengembangan Obyek Wisata Desa Haria, Kabupaten Maluku Tengah - Abraham Manuhutu; Evandro Adolf W Manuputty; Denny Richard Pattiapon (Jurnal TUNAS, 2022)
Haria village is an area that is easy to reach. By using fast sea transportation such as speed boats, tourists can arrive and enjoy the beauty of Batu Pintu, Haria Village. On the way, tourists can also enjoy the enchanting beauty of the Maluku sea. The development of the quality of the Batu Pintu tourist attraction in Haria Village is something that must be done because it has so many benefits. This description of science and technology is named Big Light, where the PKM Team wants to provide greater light for the tourist attractions in question and provide greater quality improvement of tourism services. Based on interviews, questions and answers and direct observations during this service activity, it provides results of understanding and knowledge related to Solar Cell; knowledge related to tourism development potential in Haria Village, especially Batu Pintu and understanding related to the implementation of management strategies in Haria Village tourism development. Construction followed with the installation of solar panels which was carried out jointly by the PKM team, Haria village youth, and village officials. There are 4 solar panels with a power of 60 watts that can be installed at the Batu Pintu tourist spot. After testing the system, the operation of the solar cell is left to the administrator. Meanwhile, the team will.